Penentuan Kebutuhan Poli Aluminium Klorida pada Proses Penjernihan Air di Unit Water Treatment PT. XYZ Kuala Tanjung - Nelza, Novia; Sebayang, Mariani; Yunianto; Simatupang, Dimas Frananta (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
A Water Treatment Unit (WTU) is a station that works on the processing and conditioning of raw water to meet the desired water quality. Water purification at PT. XYZ Kuala Tanjung uses raw water sourced from surface water or rivers. The river water used still contains solid substances and organic matter that render the water unsuitable for industrial use. Both suspended and colloidal solid substances can cause turbidity. Turbidity caused by solid substances can be addressed using coagulation techniques. The purpose of this research is to determine the optimal concentration and dosage of coagulant to clarify water in the WTU. The coagulant used is polyaluminum chloride (PAC). The research method is based on experiments using jar tests and stoichiometric calculations. The determination of the optimal coagulant is measured based on turbidity parameters. Experiments are conducted with varying concentrations of PAC ranging from 25-65 ppm, and the smallest turbidity value obtained is 1.21 NTU at a PAC concentration of 65 ppm, with a PAC requirement of 202.6679 kg/day. The higher the PAC concentration, the clearer the resulting water, but the daily requirement for PAC also increases.